Effect of Gang Width and Operating Speed on Specific Draft and Weeding Efficiency of Weeding Sweep in Vertisols - Yadav, S N; Pandey, M M; Saraswat, D C (Journal of Agricultural Engineering, 2005)
The study was conducted at 12%, 15%, 18% and 21% soil moisture in the clayey soil having 52.30 % clay, 11.21 % silt, 13.15 % coarse sand. The penetration resistance was kept reasonably uniform which ranges from 11.980 to 12.178 N/cm². The four gang widths i.e. 225 mm, 250 mm, 275 mm and 300 mm were taken for the study. The test was conducted at four speeds of operation i.e. 0.28 ms¯¹, 0.42 ms¯¹, 0.56 ms-1 and 0.70 ms¯¹. Hundred pins were randomly inserted in to the soil on the path of the tool in 350 mm band to represent the weed in the row. The draft was recorded by transducer designed for the present study. The undisturbed pins were counted to calculate the weeding efficiency. The effect of gang width on specific draft and weeding efficiency was observed to be significant and was linear. Specific draft was lowest for 300 mm gang width at 0.28 ms¯¹ speed and weeding efficiency was higher for 300 mm gang width at 0.42 ms¯¹ speed. It was observed that the relationship between speed and specific draft was linear and that of speed and weeding efficiency was quadratic.